Direct Deposition of CVD Diamond Layers on Top of GaN Membranes - Tibor Izsák; Gabriel Vanko; Milan Držík; Stephan Kasemann; Johann Zehetner; Marian Vojs; Bohumír Zaťko; Štěpán Potocký; Alexander Kromka (Proceedings, 2020)
We present technological issues in the deposition of diamond films on gallium nitride (GaN) membranes. Many wrinkles and thicker diamond layers were observed at the membrane center and poor quality diamond outside the membrane area. The deflection of the membranes was analyzed by a bulging method using white light interferometry. The membrane bending is discussed in the terms of temperature gradient and mismatch of thermal expansion coefficients of materials.